Severity of Trauma, Optimism, Posttraumatic Growth and Well-Being in Survivors of a Natural Disaster - Garcia Martínez, Felipe Eduardo; Universidad Santo Tomas (Pontificia Universidad Javeriana, 2013)
The aim of the study was to evaluate, in a population affected by a natural disaster, the relationship of social and psychological variables with the psychological well-being and posttraumatic growth. Participated 446 people of the province of Concepcion, Chile, affected by the earthquake on 27/F, 2010. We used the Posttraumatic Growth Inventory (PTGI), the Life Orientation Test (LOT-R) and the Flourishing Scale. We analyzed the relationship between objective severity of the event (material loss, physical damage to someone close and personal physical damage), subjective severity of the event (considering the event as traumatic or altered their lives) and dispositional optimism, showing that the interaction of optimism with subjective or objective severity contributes significantly to the prediction of well-being and growth, moderating the impact of these variables. In addition, we evaluated differences by sex, age and socioeconomic status. There was a relative influence of socioeconomic status on posttraumatic growth. This study shows the relevance of social conditions on the psychological effects of natural disasters and the importance of optimism to mitigate these effects